Novel Circulating Hypermethylated RASSF1A ddPCR for Liquid Biopsies in Patients With Pediatric Solid Tumors. (2021) - van Zogchel, Lieke M. J.; Lak, Nathalie S. M.; Verhagen, Onno J. H. M.; Tissoudali, Ahmed; Gussmalla Nuru, Mohammed; Gelineau, Nina U.; Zappeij-Kannengieter, Lily; Javadi, Ahmad; Zijtregtop, Eline A. M.; Merks, Johannes H. M.; van den Heuvel-Eibrink, Marry; Schouten-van Meeteren, Antoinette Y. N.; et al.
Abstract : PURPOSE: Liquid biopsies can be used to investigate tumor-derived DNA, circulating in the cell-free DNA (cfDNA) pool in blood. We aimed to develop a droplet digital polymerase chain reaction (ddPCR) assay detecting hypermethylation of tumor suppressor gene RASSF1A as a simple standard test to detect various pediatric tumor types in small volume blood samples and to evaluate this test for monitoring treatment response of patients with high-risk neuroblastoma. METHODS: We developed a ddPCR assay to sensitively detect tumor-derived hypermethylated RASSF1A DNA in liquid biopsies. We tested this assay in plasma of 96 patients with neuroblastoma, renal tumors, rhabdomyosarcoma, or Hodgkin lymphoma at diagnosis and in cerebrospinal fluid of four patients with brain tumors. We evaluated the presence of hypermethylated RASSF1A in plasma samples during treatment and follow-up in 47 patients with neuroblastoma treated according to high-risk protocol and correlated results with blood mRNA–based and bone marrow mRNA–based minimal residual disease detection and clinical outcomes. RESULTS: The total cfDNA level was significantly higher in patients with metastatic neuroblastoma and nephroblastoma compared with healthy adult and pediatric controls. Hypermethylated RASSF1A was present in 41 of 42 patients with metastatic neuroblastoma and in all patients with nephroblastoma, with the median percentage of 69% and 21% of total RASSF1A, respectively. Hypermethylated RASSF1A levels decreased during therapy and recurred at relapse. CONCLUSION: Our findings demonstrate the value of ddPCR-based detection of hypermethylated RASSF1A as a circulating molecular tumor marker in neuroblastoma. Our preliminary investigation of RASSF1A hypermethylation detection in circulating cfDNA of other pediatric tumor entities demonstrates potential as a pan-tumor marker, but requires investigation in larger cohorts to evaluate its use and limitations.